THE RIGHT TO COMPETENCE IN THE DEMOCRACY AND SUSTAINABILITY RELATION - Neves, Rafael Burlani; Ferrer, Gabriel Real; Ortega, Asensio Navarro (Revista de Direito Brasileira, 2022)
This article deals with the relation between democracy and sustainability in the context of an ultra-complex global society in which environmental problems are placed and, on the other hand, there is a political weakness (incompetence) to confront them. In this investigation, an approach is made about the complexities of environmental decisions in the face of a democratic crisis, as seen in recent events in some countries. It is questioned to what extent "Sustainability" and "Democracy" can converge in the political sphere, especially through the feasibility of the delivery of sustainable results in terms of sustainable development, through the competent political exercise in the political decision making of a deliberative body. It is concluded that the convergence between Sustainability and Democracy will not occur in a scenario of incompetence in decision making, although the Right to Competence is a normative element able to offer a solution to this problem. The methodology is theoretical, in order to use the dialectical method, referent techniques, documentary and bibliographic research.